P65 Static Balance Deficit In Chronic Obstructive Pulmonary Disease: Prevalence, Clinical Characteristics And Risk Of Significant Falls. (10th November 2014) - Canavan, JL; Kon, SSC; Nolan, CM; Jones, SE; Polkey, MI; Man, Wd-C
Abstract : Background: Balance deficits are associated with increased risk of falls. The tandem stand (maintaining heel to toe stance for 10 seconds or more) is an established practical measure of static balance, and is associated with increased risk of falls and disability in community dwelling adults. The aim of the study was to establish the prevalence of static balance deficit in outpatients with stable COPD and any association with exercise capacity, lower limb muscle function and health related quality of life. Furthermore, it is not known whether the tandem stand predicts future risk of significant falls in patients with COPD. Method: 174 outpatients with stable COPD (mean (SD) age 70 (9) years, FEV1 50 (21)% predicted) were stratified according to their ability to successfully complete the tandem stand. The incremental shuttle walk (ISW) test, habitual gait speed over 4 metres (4MGS), quadriceps maximal voluntary contraction (QMVC), the COPD assessment test (CAT), physical activity levels (defined as time spent in >3 METS according to the modified Minnesota Leisure-time Physical Activity Questionnaire) were also recorded. Self-reported falls and significant falls (defined as fall resulting in fracture or cerebral injury), corroborated by primary care records, were recorded over the following 12 months. Results: 24% could not complete the tandem stand. Compared to those able to complete a tandem stand, these patients were significantly older, had lower maximal exercise capacity, weaker quadriceps muscle force and reduced daily physical activity (Table 1 ). No significant falls were reported within the whole cohort, but 20 patients (11%) reported non-injury falls after 12 months of follow-up (failed tandem: 19% versus successful tandem: 9%; p = 0.10). Conclusion: Static balance deficit is common in patients with COPD, and is associated with reduced exercise capacity, quadriceps weakness and reduced daily physical activity. The tandem stand does not predict future risk of falls. Significant falls were not observed in this cohort.